RETROSPECTIVE LOOK AT THE PROBLEMS OF ETHICS IN THE LITHUANIAN PUBLIC SERVICE: NEW PROBLEMS, THEIR CONTENT AND FORMS OF EXPRESSION? - Palidauskaitė, † Jolanta (Politologija, 2015)
This article provides a retrospective look at the problems of ethics in the independent state of Lithuania, the period of Soviet Union and after the re-establishment of Lithuania’s independence. In this article, the author analyses the changing problems of ethics (red-tape, conflict of interest, bribery, abuse of authority, protectionism, corruption) in the Lithuanian public services in terms of their content, extent and forms. Although certain periods of time are characterised by smaller or larger individual problems, their essence remained almost the same throughout different stages of the public service. This conclusion points to the need to analyse the impact of Lithuanian political and administrative culture on public service ethics and other phenomena of public management.